(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The article explores the concept of mental frailty, often misunderstood as a synonym for mental illness. Through historical analysis, it highlights the revolutionary impact of Venetian psychiatrist Franco Basaglia, who transformed Italian psychiatry-understanding these mental disorders as irreversible and socially dangerous-by closing asylums thanks to Law 180/78, which allowed the possibility of other readings to the social meanings and functions of mental diversity. This law ended centuries of segregation by introducing treatment practices based on social inclusion and human dignity, offering creative solutions respectful of singular and collective needs. Psychiatria Democratica, the Association founded in 1973 by Professor Basaglia together with other practitioners, played a crucial role, opposing exclusionary institutional mechanisms towards patients and promoting Mental Health practices at the territorial level.